Investigation of the Presence of Helicobacter Pylori and the cagA Gene in Nasal Polyp Tissues by PCR - Üstündağ, Yasemin; Kavuk, Anil; Toraman, Zülal Aşçı; Tan, Mehmet; Kavuk, Yasemin; Karadağ, Kadir Ziya; Öner, Pınar (Kırşehir Ahi Evran Üniversitesi, 2026)
Purpose : Nasal polyps are inflammatory lesions of the sinonasal mucosa and may be influenced by microbial factors. Helicobacter pylori and its cagA gene are of interest because of their possible association with mucosal inflammation. This study aimed to detect H. pylori DNA and the cagA gene in nasal polyp tissues by polymerase chain reaction (PCR). Materials and Methods : This cross-sectional study included 45 nasal polyp specimens from patients undergoing surgery. Genomic DNA was extracted using a commercial kit. PCR analysis targeted the glmM gene for H. pylori detection and the cagA gene for assessment of virulence-associated genetic material. Positive and negative controls were included. Demographic variables and PCR positivity rates were evaluated descriptively, and associations with age groups were assessed statistically. Results: All samples were successfully analyzed. The group included 26 men (57.78%) and 19 women (42.22%), aged 15-75 years. glmM-based H. pylori positivity was detected in 19 samples (42.22%), whereas 26 (57.78%) were negative. cagA positivity was found in 16 samples (35.55%), whereas 29 (64.45%) were negative. Although glmM and cagA positivity rates were numerically higher in the 50-59 and 60-75-year age groups, no significant association was found between age group and PCR positivity. Conclusion: PCR analysis demonstrated H. pylori DNA and the cagA gene in a subset of nasal polyp tissues, suggesting a possible association between microbial genetic material and the chronic inflammatory microenvironment. However, PCR positivity alone does not prove viable bacteria, active colonization, or causality. Larger controlled studies integrating molecular, microbiological, and clinical parameters are needed.
Keywords: bacterial proteins; glmM; inflammation; sinusitis; virulence factors